Fintech: Its Effect on Business Sustainability - Meitriana, Made Ary; Suwena, Kadek Rai; Santi, Ni Wayan Ayu (Jurnal Pendidikan Ekonomi Undiksha, 2023)
The term "financial technology" (Fintech) is used to describe the application of innovative ICTs to the financial sector, namely to the processing of financial transactions and the promotion of new financial goods and services. Payment processing is just one of the many financial services that can be facilitated by fintech. Other examples include stock trading, financial regulation, funding and forecasting, and wealth management. In this study, we focus on fintech's application as a means of payment. The ability of micro, small, and medium-sized enterprises (MSMEs) actors to modify their activities, especially in the non-cash payment system, will be essential in the face of current technological improvements. Because the long-term success of the MSME sector could be jeopardized if industry actors do not execute the necessary reforms. As a corollary, MSME players will almost certainly be unable to compete with more developed enterprises in terms of sales transactions.